Microplastic sampling from wastewater treatment plant effluents: Best-practices and synergies between thermoanalytical and spectroscopic analysis. (1st July 2022) - Al-Azzawi, Mohammed S.M.; Funck, Matin; Kunaschk, Marco; der Esch, Elisabeth Von; Jacob, Oliver; Freier, Korbinian P.; Schmidt, Torsten C.; Elsner, Martin; Ivleva, Natalia P.; Tuerk, Jochen; Knoop, Oliver; Drewes, Jörg E.
Highlights: Best-practice framework for microplastic sampling, sample preparation and analysis. Beneficial synergies between spectroscopic and thermoanalytical analytical methods. Use of s surrogate polymer to assess removal efficiency. Abstract: Wastewater treatment plants (WWTPs) may represent point sources for microplastic discharge into the environment. Quantification of microplastic in effluents of WWTPs has been targeted by several studies although standardized methods are missing to enable a comparability of results. This study discusses theoretical and practical perspectives on best practices for microplastic sampling campaigns of WWTPs. One focus of the study was the potential for synergies between thermoanalytical and spectroscopic analysis to gain more representative sampling using the complementary information provided by the different analytical techniques. Samples were obtained before and after sand filtration from two WWTPs in Germany using cascade filtration with size classes of 5, 000 – 100 µm, 100 – 50 µm, and 50 – 10 µm. For spectroscopic methods samples were treated by a Fenton process to remove natural organic matter, whereas TED-GC-MS required only sample extraction from the filter cascade. µFTIR spectroscopy was used for the 100 µm and 50 µm basket filters and µRaman spectroscopy was applied to analyze particles on the smallest basket filter (10 µm). TED-GC-MS was used for all size classes as it is size independent. All techniques showed a similar trend, where PE was consistently the most prominent polymer in WWTP effluents. Based on this insight, PE was chosen as surrogate polymer to investigate whether it can describe the total polymer removal efficiency of tertiary sand filters. The results revealed no significant difference (ANOVA) between retention efficiencies of tertiary sand filtration obtained using only PE and by analyzing all possible polymers with µFTIR and µRaman spectroscopy. Findings from this study provide valuable insights on advantages and limitations of cascade filtration, the benefit of complementary analyses, a suitable design for future experimental approaches, and recommendations for future investigations. Graphical abstract: Image, graphical abstract